Revisión Sistemática Sobre La Fitoterapia Y Los Efectos Citotóxicos En El Tratamiento Del Cáncer Humano Con Aplicabilidad En Caninos (2022)
Cancer is the second cause of death worldwide, because it is a multifactorial pathology and for this reason it is necessary to investigate different treatments that are more effective, among them we are forced to search for new alternatives that guide us on this way. The objective of this review is to emphasize the importance of this pathology, for this reason the role played by animals is important in the scientific field. or model since neoplasms are very common in the canine species. This is why advances have been sought in different therapeutic fields in order to control this public health issue. Plants have had a significant value during ancient times in different cultures for having medicinal properties, which according to literature reports have cytotoxic properties on different cell lines such as MCF-7. Some plants can be described which contain these active ingredients such as Crotón Lechleri, Heliotropium Indicum and Pterocarpum santalinus Linn.